Progressive Increase Trend in HPV-Related Oropharyngeal Squamous Cell Carcinoma in Brazil - Pires, Rafael Cardoso; Carvalho, Raiany; Gama, Ricardo Ribeiro; Carvalho, André Lopes; Santos, Carlos Roberto; Capuzzo, Renato de Castro (International Archives of Otorhinolaryngology, 2021)
Introduction The prevalence of oropharyngeal squamous cell carcinoma (OSCC) related to Human Papillomavirus (HPV) is rising in the whole world.Objective To access the prevalence and temporal trend of HPV infection in oropharyngeal cancer by analyzing the expression of the p16 protein.Methods We conducted a transversal study in a Brazilian reference oncology center. The sample consisted of 254 patients with OSCC. The analyzed period was from 2013 to 2017. All patients underwent p16 immunohistochemistry analysis.Results The overall prevalence of HPV-related OSCC was of 31.9%. During the analyzed period, we observed a trend of increasing rates of OSCC that marked positive for p16 immunohistochemistry. The annual prevalence of p16-positive cases was of 20.6% in 2013, 23.9% in 2014, 33.3% in 2015, 38.3% in 2016, and 34.2% in 2017. Most of the patients were stage III and IV (84%). Female patients (odds ratio [OR] = 2.43; 95% confidence interval [CI]: 1.003–5.888; p = 0.049) and younger patients (OR = 2.919; 95%CI: 1.682–5.067; p < 0.005) were associated with a higher risk of HPV-related OSCC. Tobacco consumption had a proportional lower risk of HPV-related OSCC (OR = 0.152; 95%CI: 0063–0.366; p < 0.005).Conclusion We observed an increasing prevalence of HPV-related OSCC in a specialized cancer hospital in Brazil.
Keywords: oropharyngeal cancer; Human Papillomavirus; prevalence; temporal trend